تحليل العلاقة بين سعر الصرف الاجنبي و معدل التضخم: دراسة تطبيقية لمحافظة اربيل للمدة 2008-2014 (المجلة العراقية للعلوم الاقتصادية, 2018)
Analysis of the relationship between the exchange rate and the inflation rate: An Empirical Study of the province of Erbil, for the period 2008-2014This research aims to identify the causal relationship between the exchange rate of the Iraqi dinar and the inflation rate in the province of Erbil for period (2008-2014), using the cointegration. It is worth noting that the Kurdistan-Iraq region suffers from fluctuations in foreign exchange rates, and the raise of inflation rate, since the founding of the Kurdistan Regional Government in 1992. The research deals with exchange rates concept and types, as well as referring to the concept of the phenomenon of inflation, its causes, effects and the ways to treat with. Finally, the research has shown that the relationship is moving from inflation to the foreign exchange rate in the province of Erbil.